A model of financial support for the poor to access health services in Iran: Delphi technique - Etemadi, Manal; Ashtarian, Kioomars; Ganji, Nader (Clinical governance, 2023)
PurposeReducing inequity in health between the poor and the rich is one of the challenges of the Iranian health sector. Access to health services in Iran is lower in the lowest-income quarter, and the rich use health services more. The purpose of this study is to provide a comprehensive framework for enabling financial access by the poor to health services in Iran.Design/methodology/approachPolicy options were validated and approved by experts and specialists in two stages using the Delphi technique. The sample was consisted of 22 well-known experts on the subject who were selected based on purposive sampling. To evaluate the reliability of the questionnaire, a pilot study was conducted with five participants. Dimensional validity of the policy model, which was agreed upon by more than 75% of the participants was acceptable.FindingsThe main aspects of the model were divided into five categories: identifying the poor, policymaking to prevent the aggravation of health poverty, providing targeted funding, highlighting the importance of coherent regulation and ensuring financial accessibility to health services for the poor. This model could align the activities of all stakeholders in the form of a network and considers its prerequisites.Originality/valuePrevention of dire financial consequences in the case of referral to follow up the treatment alongside exemption and financial protection policies through the networking activities of organizations involved in this field is a crucial step in securing financial support for the poor. Although the researchers included a wide range of policymakers in the Delphi study to gather all perspectives about options for financially support the poor, there may be some potential neglected policy advices.